The vast majority of SARS‑CoV‑2 infections were asymptomatic in a clinic‑based cohort of people with and without HIV in four African countries - Langat, Rither; Kibuuka, Hannah; Bahemana, Emmanuel; Neha, Shah; Matthew, L. Romo (BMC Infectious Diseases, 2025)
Persons living with HIV (PLWH) were prioritized for SARS-CoV-2 vaccination in sub-Saharan Africa, however, SARS-CoV-2 infection and COVID-19 symptomatology have not been well characterized among PLWH. We described SARS-CoV-2 infection prevalence and symptomatology, and examined factors associated with nasal swab RT-PCR positivity in Kenya, Uganda, Tanzania, and Nigeria. The ongoing African Cohort Study (AFRICOS) follows PLWH and people living without HIV (PLWoH) in four African countries. All participants undergo clinical assessment and socio-behavioral questionnaire administration at enrollment and each six-monthly visits, with CD4 count and viral load collected for PLWH. Optional nasal swabs were collected for SARS-CoV-2 rapid RT-PCR testing at visits after 19 July 2022. Participants were asked if they had experienced COVID-19 symptoms. We used the Agresti-Coull method to estimate the prevalence of SARS-CoV-2 infection at each participant’s first nasal swab collection. Adjusted prevalence ratios (aPRs) and 95% confidence intervals (CIs) for factors potentially associated with SARS-CoV-2 infection were estimated using multivariable robust Poisson regression. Between 19 July 2022 and 1 March 2024, 1,187 participants underwent nasal swab collection with a valid SARS-CoV-2 RT-PCR result; 1,032 (86.9%) were PLWH and 155 (13.1%) were PLWoH. A majority were female (57.2%), and the median age was 44.6 (interquartile range 34.4–52.2) years. Prevalence at first nasal swab of SARS-CoV-2 was 6.8% (95%CI 5.5%-8.4%). Most participants with positive SARS-CoV-2 RT-PCR were asymptomatic (97.5%). SARS-CoV-2 was marginally more common among PLWoH as compared to PLWH (10.3% vs. 6.3%; p = 0.093). In the multivariable model, SARS-CoV-2 was significantly more common among participants who received at least one dose of a COVID-19 vaccine as compared to participants who received no doses (aPR 1.66; 95%CI 1.05–2.62; p = 0.031) and during the omicron wave as compared to non-wave periods (aPR 2.15; 95%CI 1.42–3.25; p < 0.001). Among PLWH, CD4 and viral load were not associated with SARS-CoV-2 prevalence. The vast majority of people with positive SARS-CoV-2 RT-PCR were asymptomatic. Universal screening may be needed to fully understand the epidemiology of SARS-CoV-2 and future outbreaks of similar respiratory viruses, capture early infection, and plan for intervention.